EDUCAÇÃO AMBIENTAL NA ESCOLA: DA COLETA SELETIVA DO LIXO AO APROVEITAMENTO DO RESÍDUO ORGÂNICO - Brum, Danilieta Pereira; Silveira, Djalma Dias (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This study aimed to implement Environmental Education in School State Elementary SchoolCaptain Emídio Jaime de Figueiredo. By observing the behavior of the community surroundingthe school, especially regarding the fate of the waste produced by households, and to analyze thequestionnaires that were used for data collection, it was observed that residents had not yetsufficient clarification regarding the subject matter, although some feel the need to change thisreality. For this was provided to the school community a lecture for clarification and anecological walk around the neighborhood with the participation of teachers and students, weredistributed pamphlets containing information on issues such as recycling, composting, and howthe selective collection is being streamlined this work in the city. There is a clear need for theschool working to provide the community with an environmentally conscious school, aiming totransform the current reality, respect the environment and improving the quality of life ofresidents.